Socially-oriented approach to financial risk management as the basis of support for the sdgs in entrepreneurship - Anna N. Zhilkina; Marina V. Karp; Anna V. Bodiako; Samal M. Smagulova; Tatiana M. Rogulenko; Svetlana V. Ponomareva (Risks, 2022)
This paper demonstrates that the level of financial risks and the impact of the COVID-19 pandemic and crisis on them are high. The existing approach to financial risk management is not very effective and does not allow coping with financial risks in entrepreneurship, not even in a certain category of countries. As a prospective alternative, we offer a new socially-oriented approach. The theoretical value of the paper lies in the offering and scientific substantiation of a new hypothesis: that the SDGs could and should be constantly supported by business in their financial risk management with the help of the socially-oriented approach, which is available and expedient for use under the conditions of economic crisis. The practical value of the received results is as follows: the developed new (alternative) socially-oriented approach to financial risk management in entrepreneurship allows increasing the effectiveness of financial risk management in entrepreneurship and raising its robustness against the current COVID-19 crisis. The social importance of the obtained conclusions and results is that the developed approach allows for and stimulates continuous support for the SDGs in entrepreneurship.
Keywords: 330; entrepreneurship; financial risk management; socially-oriented approach; support for the SDGs